Effect of ammonium sulphate fortification on growth performance, nutrient digestibility and nitrogen balance of West African dwarf rams (2016)
Ammonium sulphate (NH(4)2SO(4) is potential source of readily available nitrogen and sulphur which would fill the gap in feed availability to ruminants during the extended annual dry season. Hence, the use of ammonium sulphate becomes a viable alternative to growth-promoting antibiotics due to their effectiveness on ruminant productivity. Therefore, the effect of various inclusion levels of ammonium sulphate on the performance of West African Dwarf (WAD) rams was examined. Sixteen rams weighing 12.8±0.1-2 kg were assigned to four experimental diets containing 0.00, 0.25, 0.50 and 0.75% levels of ammonium sulphate designated as Tl, T2, T3 and T4 respectively. In a completely randomized design, each rams were fed at 5% of their body weight at 60:40 levels of experimental diet and wilted guinea grass as basal diet. The growth trial lasted for 105 days. The chemical composition of the experimental feed and faecal samples were analyzed, and data on total voluntary feed intake, feed conversion ratio, weight gain, nitrogen utilization, and apparent digestibility were also collected. The parameters on proximate composition of the feed were significantly affected by the inclusion of (NH(4)2SO(4) except for DM, GE, Calcium (Ca) and Phosphorus (P). The values for the parameters increased with increased inclusion of (NH(4)2SO(4). The dry matter (DM) and crude protein (CP) obtained ranged from 94.15 - 94.69% and 11.00 - 13.40% respectively while the levels of sulphur was between 4.13 - 4.85%. Live weight gain increased with increased inclusion of (NH(4)2SO(4) and ranged from 3.50 - 5.00 kg but did not differ significantly (P>0.05) from each other. The total voluntary feed intake (TVFI) obtained in this study ranged between 59.79 - 62.64 kg and feed conversion ratio (FCR) from 11.96 - 17.90. However, TVFI and FCR decreased with increasing levels of (NH(4)2SO(4) in the diet. Also, acid detergent lignin digestibility was significantly (P<0.05) affected by inclusion levels of ((NH(4)2SO(4) in the treatments. Nitrogen in feed (3.39g/day), faecal nitrogen output (2.62g/day), urinary nitrogen output (0.21g/day) and nitrogen retention (0.56g/day) were insignificantly (P>0.05) difference except percentage nitrogen retained (16.52g/day) which is significantly different (P<0.05) from each other. It is evident that rams on 0.75% ammonium sulphate supplementation had better growth performance, improved nutrient digestibility and nitrogen metabolism, hence substantiating its utilization in ram diet.